2020
DOI: 10.1111/iej.13271
|View full text |Cite
|
Sign up to set email alerts
|

Application of a new system for classifying root canal morphology in undergraduate teaching and clinical practice: a national survey in Malaysia

Abstract: AimTo evaluate and compare the feedback of final year undergraduate dental students in eight Malaysian dental schools on the application of a new system for classifying root canal morphology in teaching and clinical practice.MethodsOne PowerPoint presentation describing two classification systems for root canal morphology (Oral Surgery Oral Medicine Oral Pathology, 1974 38, 456 and its supplemental configurations, International Endodontic Journal 2017, 50, 761) was delivered to final year undergraduate dental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 29 publications
3
33
0
Order By: Relevance
“…The classification of root canal anatomy proposed by Ahmed et al (2017) was preferred because it elegantly describes the three-dimensional complexity of the root canal system. Recently, the new system was evaluated by dental students in Malaysia (Ahmed et al 2020) and was reported to be highly beneficial for their understanding of root canal anatomy. These findings are promising and need to be further evaluated, especially with the introduction of VR in endodontic education.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The classification of root canal anatomy proposed by Ahmed et al (2017) was preferred because it elegantly describes the three-dimensional complexity of the root canal system. Recently, the new system was evaluated by dental students in Malaysia (Ahmed et al 2020) and was reported to be highly beneficial for their understanding of root canal anatomy. These findings are promising and need to be further evaluated, especially with the introduction of VR in endodontic education.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the new system was evaluated by dental students in Malaysia (Ahmed et al . 2020) and was reported to be highly beneficial for their understanding of root canal anatomy. These findings are promising and need to be further evaluated, especially with the introduction of VR in endodontic education.…”
Section: Discussionmentioning
confidence: 99%
“…A recent national survey study in Malaysia compared feedback from undergraduate dental students on a new system for classifying the root and canal morphology with that of the Vertucci classification and its supplemental configurations (Ahmed et al . 2020). The results revealed that more than 90% of students believed that the new system for classifying root and canal morphology was more accurate and more practical compared with the Vertucci classification.…”
Section: Figurementioning
confidence: 99%
“…The lecture was delivered in Spanish, and the questionnaire used in Ahmed et al . (2020) was translated into Spanish and distributed electronically to participants (Ethical approval number 172‐2020). The lecture was attended by 300 participants and a total of 239 participants responded to the questionnaire (response rate = 79.7%).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation